2019
DOI: 10.1074/jbc.ra118.004902
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor (HIF)-prolyl hydroxylase 3 (PHD3) maintains high HIF2A mRNA levels in clear cell renal cell carcinoma

Abstract: Most clear cell renal cell carcinomas (ccRCCs) have inactivation of the von Hippel-Lindau tumor suppressor protein (pVHL), resulting in the accumulation of hypoxia-inducible factor ␣-subunits (HIF-␣) and their downstream targets. HIF-2␣expression is particularly high in ccRCC and is associated with increased ccRCC growth and aggressiveness. In the canonical HIF signaling pathway, HIF-prolyl hydroxylase 3 (PHD3) suppresses HIF-2␣ protein by post-translational hydroxylation under sufficient oxygen availability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…For the mentioned five up- and eleven down-regulated circRNAs, the circRNA IDs used in the databases ArrayStar and circBase [22] are summarized in Table 2. To identify circRNAs with a putative function in ccRCC initiation/progression, we selected circRNAs from host genes with putative roles in angiogenesis and hypoxia in ccRCC and other cancers including EGLN3 , NOX4 , and RHOBTB3 [23,24,25,26,27]. Thus, corresponding circRNAs of the three host genes that are named according to the database circBase hsa_circ_0101692, hsa_circ_0023984, and hsa_circ_000744 were selected for further validation (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the mentioned five up- and eleven down-regulated circRNAs, the circRNA IDs used in the databases ArrayStar and circBase [22] are summarized in Table 2. To identify circRNAs with a putative function in ccRCC initiation/progression, we selected circRNAs from host genes with putative roles in angiogenesis and hypoxia in ccRCC and other cancers including EGLN3 , NOX4 , and RHOBTB3 [23,24,25,26,27]. Thus, corresponding circRNAs of the three host genes that are named according to the database circBase hsa_circ_0101692, hsa_circ_0023984, and hsa_circ_000744 were selected for further validation (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the in-silico analysis for circEGLN3 predicted a potential binding of miR-31-5p and miR-1205 to circEGLN3 and the corresponding linear RNA of EGLN3. EGLN3 is known to contribute to ccRCC initiation [25,26,54] by targeting HIF. The up-regulation of both circEGLN3 and linRNA of EGLN3 in ccRCC and the predicted interaction via miR-31-5p and miR-1205 could reflect a self-sustaining mechanism of the oncogene EGLN3.…”
Section: Discussionmentioning
confidence: 99%
“…In response to hypoxia situation, hypoxia-inducible factor (HIF) is upregulated to coordinate an appropriated adaptive response 3. HIF is a highly conserved transcription factor comprising a regulatory α subunit (HIF1α, HIF2α, or HIF3α) and a constitutive β subunit (HIF-β) 4. It has been reported that hypoxia-induced overexpression of HIF1α promotes epithelial–mesenchymal transition in FTC 5.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study reported that PHD3 was highly expressed in serum from RCC patients and could be a novel biomarker with the valuable diagnostic performance, 33 and its high level might reinforce ccRCC aggressiveness. 34 Moreover, a tissue-wide expression profiling was generated using cDNA subtraction and microarrays, and EGLN3 was discovered to be highly regulated in RCC samples. 35 These observations suggested that RCC was associated with a high level of EGLN3 .…”
Section: Discussionmentioning
confidence: 99%